2022
DOI: 10.1186/s40824-022-00270-w
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Mediated drug release and tumor theranostics using melanin-loaded liposomes

Abstract: Background Heat generation in a drug delivery carrier by exposure to near-infrared (NIR) light with excellent tissue transmittance is an effective strategy for drug release and tumor therapy. Because liposomes have amphiphilic properties, they are useful as drug carriers. Liposomes are also very suitable for drug delivery strategies using heat generation by NIR laser because lipid bilayers are easily broken by heat. Thermally generated bubbles from liposomes not only induce drug release, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It is seen that the NIR-II irradiation also triggers ROS generation in the biological tissue, which is an intriguing approach to employing NIR-II-based therapeutic activation and imaging. Despite the ease of operability of ultrasound imaging in observing SDT activity 40 , the technique primarily suffers from low resolution and interference from surrounding tissues (Figure 2 B and 2 C). Technological advancements such as bio adhesive ultrasound are intriguing approach for on-body continuous organ monitoring 45 .…”
Section: Bioimagingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is seen that the NIR-II irradiation also triggers ROS generation in the biological tissue, which is an intriguing approach to employing NIR-II-based therapeutic activation and imaging. Despite the ease of operability of ultrasound imaging in observing SDT activity 40 , the technique primarily suffers from low resolution and interference from surrounding tissues (Figure 2 B and 2 C). Technological advancements such as bio adhesive ultrasound are intriguing approach for on-body continuous organ monitoring 45 .…”
Section: Bioimagingmentioning
confidence: 99%
“…(B) IR thermal images showing Melanin, Perfluorohexane (PFH) and 5-fluorouracil (5-FU) loaded liposomes (melanin@PFH@5-FU-liposomes) generating heat upon NIR 808 nm light. (C) Ultrasound images of tumor tissues in CT26-bearing mice before and after laser irradiation at 1 h, 4 h, and 12 h after intravenous injection of melanin@PFH@5-FU-liposomes 40 . Copyright 2022, Springer Nature.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…designed prepared based on a thin film method and utilizing Melanin, perfluorohexane (PFH), and 5-fluorouracil (5-FU)loaded liposomes (melanin@PFH@5-FU-liposomes). The result indicated that tumor growth was virtually inhibited by the injection of melanin@PFH@5-FU-liposomes with laser irradiation (Kim and Lee, 2022). PFC nanoemulsions are utilized in both liquid NPs and gas bubble forms.…”
Section: Cancermentioning
confidence: 99%
“…Light stimuli-responsive remote control is a method for manipulating specific events, processes, or functionalities within a biological system. It offers non-invasiveness, controllability, non-toxicity, and high spatiotemporal resolution [ 9 11 ]. We meticulously engineered the C820 nanoparticles as a chemo-photothermal nanoplatform, incorporating cisplatin (CDDP), linoleic acid (LA), and the photothermal agent IR820.…”
Section: Introductionmentioning
confidence: 99%